The Progression and Ongoing Development of a Research Agenda for Faith Community Nursing. Issue 3 (July 2020) - Solari-Twadell, Phyllis Ann; Ziebarth, Deborah Jean
Abstract : ABSTRACT: Research is critical to the growth of professional nursing in every practice area. Faith community nursing research evolved slowly in the years following publication of the first research in 1989. A faith community nursing research agenda was developed in 2008 and research priorities have been reviewed every 2 years since 2012 at a forum held in conjunction with the annual Westberg Symposium. This article reviews the progression and ongoing development of a research agenda for the specialty practice of faith community nursing. Recommendations for the development of future research for faith community nursing are discussed.